Analysis of Content Representation (CoRes) and TPACK (Technological Pedagogical Content Knowledge) in Biotechnology Material - Dini Nurani Rahmawati; Najira Najira; Mahda Rizqina Maftuha; Adi Rahmat; Riandi Riandi (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
TPACK is a complete combination of knowledge and skills in the field of material and teaching strategies that are adapted to technological developments. The purpose of this article is to analyze the breadth and depth of molecular biotechnology material in CoRe to find out important concepts that need to be taught to students to summarize modern biotechnology learning with molecular biotechnology sub-material and present TPACK, which has been analyzed and reconstructed. This research method uses a qualitative approach and a literature study. Biotechnology material is difficult to understand and is abstract, especially molecular biotechnology material. Meanwhile, teachers are still not using appropriate learning strategies in the field. So, teachers must have skills in designing effective learning to achieve learning goals. By analyzing which the teacher will provide essential content through Content Representation (CoRes) and then combining it with selecting appropriate learning strategies based on TPACK (Technological Pedagogical and Content Knowledge), it can help students understand biotechnology material that they find difficult and can be referenced for teachers to select appropriate learning models, media, and learning approach.